Benefit of low‐dose tamoxifen in a large observational cohort of high risk ER positive breast DCIS. Issue 9 (19th July 2016) - Guerrieri‐Gonzaga, Aliana; Sestak, Ivana; Lazzeroni, Matteo; Serrano, Davide; Rotmensz, Nicole; Cazzaniga, Massimiliano; Varricchio, Clara; Pruneri, Giancarlo; Leonardi, Maria Cristina; Orecchia, Roberto; Galimberti, Viviana; Bonanni, Bernardo; et al.
Abstract : Low‐dose tamoxifen has comparable antiproliferative effect to the standard dose of 20 mg/day in biomarker trials, but its clinical efficacy remains unclear. We assessed the effect of low‐dose tamoxifen on ipsilateral recurrence in ductal carcinoma in situ (DCIS) patients treated in a referral Institution between 1996 and 2008. Following conserving surgery, women received radiotherapy and/or low‐dose tamoxifen upon clinical judgment and patient preferences. Cox regression analyses were used with and without confounding factors. Among 1, 091 women with DCIS and median age 53 years (IQR: 46–62), 544 (49.9%) received radiotherapy. Of the 833 women with oestrogen receptor (ER) positive DCIS, 467 (56.1%) received low‐dose tamoxifen. After a median of 7.7 years, 235 ipsilateral recurrences and 62 contralateral breast tumors were observed. Low‐dose tamoxifen significantly decreased any breast event (HR = 0.70, 95% CI: 0.54–0.91) and ipsilateral DCIS recurrence (HR = 0.66, 95% CI: 0.49–0.88), but not ipsilateral invasive recurrence or contralateral tumors. Radiotherapy showed a large significant reduction for any breast event (HR = 0.55, 95% CI: 0.42–0.72). Tamoxifen was more effective on all breast events in women aged >50 years than in women aged ≤50 (HR = 0.51, 95% CI: 0.33–0.77 versus HR = 0.84, 95% CI: 0.60–1.18, p ‐interaction = 0.03). Age ≤50 years, positive margins, high Ki67, high grade and low BMI were independent predictors of ipsilateral recurrence. No increase of endometrial cancers and fewer deaths ( p  = 0.015) were observed on tamoxifen. Low‐dose tamoxifen seems to be safe and effective in reducing ipsilateral recurrence in ER positive DCIS in women aged >50 years. A randomized trial is underway to confirm these findings. Abstract : What's new? Ductal carcinoma in situ may be treated with surgery, but there's no agreement on what should follow surgery. How best to prevent the cancer from returning? These authors looked at what happened when patients with a high risk of recurrence received low‐dose tamoxifen following surgery. Women over age 50 experienced a 50% reduction in their risk of the cancer returning, while in younger women the benefit from the tamoxifen was much less. This observational study provides good evidence to warrant a follow‐up study, and a randomized clinical trial is underway to further investigate these findings.